Continuidade da estimulação neuropsicomotora de crianças com síndrome congênita do Zika: o olhar de cuidadores e de profissionais - Guedes, Anna Tereza Alves (2020)
Introduction: The continuity of the stimulation of neuropsychomotor development occurs through communication between the health professionals, the user and the family, aiming to achieve goals in a shared way, ensuring effective results in the development of children with congenital Zika syndrome and improve your life quality. Objective: To understand the continuity of the stimulation of neuropsychomotor development of children with congenital Zika syndrome and to understand the perception about the development of these children, from the perspective of caregivers and professionals of rehabilitation services. Methodological path: Descriptive-exploratory research, based on the theoretical assumptions of Symbolic Interactionism, performed with 12 professionals in three public institutions in a capital of Northeast Brazil and with seven caregivers of children with congenital Zika syndrome. Data were collected from August to November 2019, through an profound interview with professionals, and a focus group with caregivers. The empirical material was analyzed using the technique of inductive thematic analysis. In compliance with ethical observances, the project was assessed and approved by the Research Ethics Committee, under CAAE nº. 17008919.9.0000.5188. Results: It was observed that the study participants consider that there is a severe impairment of the child's neuropsychomotor development with the congenital Zika syndrome, and that there are obstacles to achieving success in the stimulation of these children, related to organizational barriers, socio-environmental aspects and difficulties imposed by their own child's condition. The complementary integrative therapies may contribute to the development of these children. Final considerations: Due to the difficulties faced to continue the stimulation of children with congenital Zika syndrome, a strengthened support network is needed, with development stimulation associated with complementary therapies and qualified human resources, in order to offer comprehensive care to this group.